(untitled) (Analytic Teaching, 1988)
Introduction: In his discussion with Harry and Lisa, Mickey makes several statements about how we know if something is right. His view can be summarized into three main points: 1) if it feels good, then it’s right; 2) what is wrong fails and what is right succeeds; and, 3) wrong ideas won’t work. This view is often attributed to pragmatism, which holds that ideas can be judged by how well they satisfy our purposes. Yet the pragmatism of Pierce, James, and Dewey departs significantly from the crude hedonism that Mickey is espousing. Dewey, in particular, is concerned to do two things in the realm of value theory: 1) to overcome subjectivism by placing the biological and psychological origins of value within a framework of rational inquiry, and 2) to refute the transcendental and emotive theories of value by defining means and ends functionally rather than substantially. Dewey denies the distinction between instrumental and final ends; the only things that count are values that work in human affairs by ameliorating ills and problems. What "works" is not determined by mere expedience, but by reflection upon all of the consequences of the means we have chosen to produce specific ends.